Measuring Self-Efﬁcacy to Deal With Infertility: Psychometric Properties and Conﬁrmatory Factor Analysis of the Portuguese Version of the Infertility Self-Efﬁcacy Scale - Galhardo, Ana (2013)
This study explores the psychometric properties and factor structure of the Portuguese version of the Infertility Self-Efﬁcacy Scale (ISE-P), using translation and back-translation of the original version; principal component analysis; conﬁrmatory factor analysis (CFA); and internal consistency, and test–retest reliability analyses. A total of 287 participants (156 women and 131 men) seeking medical treatment were recruited from public and private fertility centers. CFA revealed that the single-component model ﬁt the data well. The instrument showed excellent internal consistency, good test–retest reliability, and correlations with other mental health measures suggesting good convergent and discriminant validity. In conclusion, The ISE-P is a valid and reliable Portuguese-language measure of perceived self-efﬁcacy to cope with infertility.